The principle of justice and health in Chile - Lavados Montes, Claudio; Gajardo Ugás, Alejandra (Acta Bioethica, 2008)
Equality in access to health care, efficiency in interventions designed to promote, preserve and recuperate health, and the efficient use of available health care resources are the central objectives of the Health Care System Reform in Chile, based on the principle of justice. This article deals with the theme of justice in health, starting from the traditional definition, continuing to that of healthcare, and culminating in what bioethics interprets today as justice, and whether this principle is verified or not under Plan AUGE, as the Political Constitution of Chile establishes the right to health care as a basic right recognized for all citizens.